Jackaby - Ritter, William, 1984- (2015)
Newly arrived in 1892 New England, Abigail Rook becomes assistant to R.F. Jackaby, an investigator of the unexplained with the ability to see supernatural beings, and she helps him delve into a case of serial murder which, Jackaby is convinced, is due to a nonhuman creature.
Keywords: Mystery and detective stories; Serial killers -- Fiction; Murder -- Fiction; Supernatural -- Fiction; Imaginary creatures -- Fiction; New England -- History -- 19th century -- Juvenile fiction; New England -- History -- 19th century -- Fiction